Benthic macroinvertebrate communities in the littoral zone of Greek lakes - A. Patsia; D. Kemitzoglou; E. Mavromati; V. Tsiaoussi (Ελληνικό Κέντρο Βιοτόπων-Υγροτόπων (ΕΚΒΥ), 2023)
Patsia A., D. Kemitzoglou, E. Mavromati, and V. Tsiaoussi. 2023. Benthic macroinvertebrate communities in the littoral zone of Greek lakes. 19th World Lake Conference, Balaton, Hungary, 7-9 November 2023. Poster presentation